2022
DOI: 10.3748/wjg.v28.i21.2302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiotherapy on the immune landscape in oesophageal adenocarcinoma

Abstract: BACKGROUND In the contemporary era of cancer immunotherapy, an abundance of clinical and translational studies have reported radiotherapy (RT) and immunotherapies as a viable option for immunomodulation of many cancer subtypes, with many related clinical trials ongoing. In locally advanced disease, chemotherapy or chemoradiotherapy followed by surgical excision of the tumour remain the principal treatment strategy in oesophageal adenocarcinoma (OAC), however, the use of the host immune system to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Additional studies also identified that irradiation stimulates tumour cells and immune cells to secrete RANTES and MIP-1α [20], which suggests that irradiation might promote the trafficking of T cells to OAC tumours. In a previous study, we observed that irradiating OAC tumour biopsy explants ex vivo had favourable effects on the secretome, significantly increasing the secretion of anti-tumour cytokines IL-21 and IL-31 [21] and decreasing the production of a tumour-promoting cytokine IL-23 [21]. In addition, radiation induced an anti-angiogenic tumour milieu by reducing the secretion of VEGF-A, BFGF, Flt-1, and PIGF pro-angiogenic factors [21].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additional studies also identified that irradiation stimulates tumour cells and immune cells to secrete RANTES and MIP-1α [20], which suggests that irradiation might promote the trafficking of T cells to OAC tumours. In a previous study, we observed that irradiating OAC tumour biopsy explants ex vivo had favourable effects on the secretome, significantly increasing the secretion of anti-tumour cytokines IL-21 and IL-31 [21] and decreasing the production of a tumour-promoting cytokine IL-23 [21]. In addition, radiation induced an anti-angiogenic tumour milieu by reducing the secretion of VEGF-A, BFGF, Flt-1, and PIGF pro-angiogenic factors [21].…”
Section: Introductionmentioning
confidence: 92%
“…In a previous study, we observed that irradiating OAC tumour biopsy explants ex vivo had favourable effects on the secretome, significantly increasing the secretion of anti-tumour cytokines IL-21 and IL-31 [21] and decreasing the production of a tumour-promoting cytokine IL-23 [21]. In addition, radiation induced an anti-angiogenic tumour milieu by reducing the secretion of VEGF-A, BFGF, Flt-1, and PIGF pro-angiogenic factors [21].…”
Section: Introductionmentioning
confidence: 92%
“…Several studies found immune checkpoints, such as PD-1, CTLA-4, TIGIT, TIM-3, LAG-3 or ICOS, to be significantly upregulated in infiltrating T cells following NAC ( 46 , 47 ). An OAC cell line study validated ex-vivo also suggested increased expression of several immune checkpoint expression following radiotherapy ( 48 ). Soeratram et al.…”
Section: Treatment Evolution In Oac and Modulation Of The Tmementioning
confidence: 98%
“…RNA sequencing and flow cytometry analysis showed that TIGIT of CD8 + T cells increased on day 7 after 8 Gy × 3 RT while 2 Gy × 18 irradiation treatment resulted in a drop in TIGIT expression over time (day 7, day 14 and day 30) [ 120 ]. In two cohorts of esophageal cancer, the expression of PD-1, PD-L1, TIGIT and TIM-3 was downregulated in CD3 + CD4 + T and CD3 + CD8 + T cells in patients well responding to 2 and 4 Gy RT while PD-1, PD-L1 and TIGIT were elevated in those poorly [ 127 ]. 10 Gy RT combined with αPD-L1 led to a 2- and 2.4-fold upsurge in the expression of TIM-3 in CD8 + T cells and Tregs, respectively, indicating upregulation of TIM-3 mediated resistance to PD-L1 blockade [ 122 ].…”
Section: Effect Of Radiotherapy On Immune Checkpoint Molecules In The...mentioning
confidence: 99%